2011
DOI: 10.1002/esp.2147
|View full text |Cite
|
Sign up to set email alerts
|

Modelling wind-blown sediment transport around single vegetation elements

Abstract: Wind erosion is an important soil erosion and hence a soil degradation problem in the Sahelian zone of West Africa. Potentially, the characteristic dryland vegetation with scattered trees and shrubs can provide for soil erosion protection from wind erosion, but so far adequate quantification of vegetation impacts is lacking. The aim of this study was to develop a model of windblown soil erosion and sediment transport around a single shrub-type vegetation element. Starting with the selection of a suitable trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 56 publications
(107 reference statements)
7
77
1
1
Order By: Relevance
“…The total amount of sediment eroded from a given cell is calculated deterministically as a function of the cell ' s wind velocity, using the semiempirical flux relationship of Dong et al []: Q=aD1utu20.25em(),ρairgu3 where Q is the predicted mass flux for the given time interval (kg m −1 s −1 ), u is the mean horizontal wind velocity over the given time interval (m s −1 ), u t is the horizontal velocity threshold for sediment entrainment (m s −1 ), ρ air is the density of air (1.25 kg m −3 ), g is acceleration due to gravity (9.81 m s −2 ), and a D is an empirically fitted constant. Dong et al 's [] model has been shown to perform well over a variety of averaging intervals using field‐based wind velocity data [ Leenders et al ., ; Mayaud et al ., ].…”
Section: Model Descriptionmentioning
confidence: 99%
“…The total amount of sediment eroded from a given cell is calculated deterministically as a function of the cell ' s wind velocity, using the semiempirical flux relationship of Dong et al []: Q=aD1utu20.25em(),ρairgu3 where Q is the predicted mass flux for the given time interval (kg m −1 s −1 ), u is the mean horizontal wind velocity over the given time interval (m s −1 ), u t is the horizontal velocity threshold for sediment entrainment (m s −1 ), ρ air is the density of air (1.25 kg m −3 ), g is acceleration due to gravity (9.81 m s −2 ), and a D is an empirically fitted constant. Dong et al 's [] model has been shown to perform well over a variety of averaging intervals using field‐based wind velocity data [ Leenders et al ., ; Mayaud et al ., ].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Arens et al, 2001b;Dong et al, 2008;Dupont et al, 2014;Lancaster and Baas, 1998;Leenders et al, 2011;Luo et al, 2014;Okin, 2008;Van Dijk et al, 1999), it remains difficult to predict patterns of erosion and deposition for varying wind conditions and on irregularly vegetated surfaces, such as foredunes Leenders et al, 2011). However, such predictions are a prerequisite for modelling foredune development, as erosion and sedimentation patterns eventually determine foredune morphology and evolution (Hesp, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have reported that vegetation has the capacity to decrease soil loss by wind as it reduces wind speed and soil erodibility, and increases the entrapment of eroded material (Van De Ven et al, 1989;Sterk et al, 1998;Udo and Takewaka, 2007;Abdourhamane Toure et al, 2011;Leenders et al, 2011;Munson et al, 2011). Research on stabilization of moving sand dunes has also linked reduction of sand movement to the increased trapping capacity of vegetation cover (Hesse et al, 2004;Chang et al, 2011;Drenova, 2011;Floyd and Gill, 2011).…”
Section: Introductionmentioning
confidence: 99%